2016
DOI: 10.1159/000446099
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytogenetic Analysis of Spontaneous Abortions in Recurrent and Sporadic Pregnancy Losses

Abstract: Background: The majority of miscarriages are sporadic; however, 1-5% of couples experience recurrent pregnancy loss (RPL). Approximately 50-60% of miscarriages result from chromosomal abnormalities. Currently, there are conflicting reports regarding the rates of chromosomal abnormalities between recurrent and sporadic pregnancy losses. Methods: A retrospective comparative cytogenetic analysis of 442 RPL and 466 sporadic abortions (SA) was performed. Maternal age and medical background were evaluated, and chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 41 publications
6
32
3
3
Order By: Relevance
“…In contrast, reports of aneuploidy associated with pregnancy loss in domesticated animals is rarely reported, and never in the horse. Here we identified autosomal aneuploidies in 20% of naturally occurring equine EPL conceptuses, slightly lower than the 35-50% reported in women [20, 45] possibly explained by the shorter gestational time frame used in our study. Seven of the aneuploidy types we described were unique to the study, including two monosomies.…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, reports of aneuploidy associated with pregnancy loss in domesticated animals is rarely reported, and never in the horse. Here we identified autosomal aneuploidies in 20% of naturally occurring equine EPL conceptuses, slightly lower than the 35-50% reported in women [20, 45] possibly explained by the shorter gestational time frame used in our study. Seven of the aneuploidy types we described were unique to the study, including two monosomies.…”
Section: Discussioncontrasting
confidence: 78%
“…However, conflicting results have been reported. Nikitina et al (20) reported that the frequency of abortions with normal karyotypes was significantly higher in maternal patients with recurrent miscarriages as compared to that in patients with SM (53. (24) and Grande et al (25) reported conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical chromosome anomalies are the most common cause of spontaneous abortion, but this is not the case for repeated miscarriages. As the number of miscarriages increases, the probability of further spontaneous abortions with normal karyotype and the probability to lose the next pregnancy increase as well [Nikitina et al, 2016]. However, if one member of the couple is a carrier of structural chromosome abnormalities (balanced transloca- tions, inversions, marker chromosomes, etc.…”
Section: Discussionmentioning
confidence: 99%